2016
DOI: 10.1093/jac/dkw258
|View full text |Cite
|
Sign up to set email alerts
|

Impact of AAC(6′)-Ib-cr in combination with chromosomal-mediated mechanisms on clinical quinolone resistance inEscherichia coli

Abstract: The aac(6')-Ib-cr gene, in spite of producing low-level resistance by itself, plays a relevant role in acquisition of a clinical level of ciprofloxacin and norfloxacin resistance, when combined with three or four chromosomal mutations, both in vitro and in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 17 publications
0
26
0
1
Order By: Relevance
“…Studies showed that PMQR was usually low level, and its MIC value was below the CLSI resistance breakpoint [21]. The MIC of c749 demonstrated intermediate resistance, which indicated that the coexistence of three PMQR genes can cause an increase in MIC more than the presence of one or two PMQR genes reported [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Studies showed that PMQR was usually low level, and its MIC value was below the CLSI resistance breakpoint [21]. The MIC of c749 demonstrated intermediate resistance, which indicated that the coexistence of three PMQR genes can cause an increase in MIC more than the presence of one or two PMQR genes reported [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…A similar positive epistatic effect was observed for chromosomal gyrA / parC mutations together with plasmid-mediated resistance determinants qepA 67 and aac(6’)Ib-cr . 52,75 However, experimental studies of combinations of gyrA and parC mutations with qnr genes showed discordant results. One study reported a negative epistatic effect on ciprofloxacin MIC of target alteration mutations with all qnr genes tested ( qnrA , qnrB , qnrC , qnrD , qnrS ) 59 , and another study observed a similar effect of target alteration mutations with qnrB , but the opposite effect for target alteration mutations with qnrS in terms of conferred MIC.…”
Section: Discussionmentioning
confidence: 99%
“…Studies showed that PMQR was usually low level, and its MIC value was below the CLSI resistance breakpoint [20]. The MIC of c749 demonstrated intermediate resistance, which indicated that the coexistence of three PMQR genes can cause an increase in MIC more than the presence of one or two PMQR genes reported [21,22].…”
Section: Discussionmentioning
confidence: 99%